Hots Solving Mathematical Category Problems - Yusuf Fuad; Rooselyna Ekawati (Budapest International Research and Critics University, 2022)
The quality of education in Indonesia is still not good when seen from the ranking results released by PISA (Program for International Students Assessment) where the indicators used by PISA to assess are reading, math and science skills. The assessment of mathematical ability in the PISA survey uses HOTS questions, and based on Bloom's Taksono.mi to solve the HOTS category questions a higher cognitive level is needed than the LOTS questions, the cognitive level needed is at levels C4-C6, which means that HOTS questions will be able to completed by students with high cognitive levels which are generally known as students who have a high IQ. This study uses a mixed method sequential explanatory, where the researcher collects and analyzes quantitative data, then proceeds to collect and analyze qualitative data. The results of quantitative research prove that IQ levels affect students' mathematical communication skills in solving HOTS questions, and from qualitative research, it is known that the main obstacles experienced by students in performing mathematical communication are, students do not understand the material and are less able to perform mathematical operations calculations, Students who understand the material will be able to understand the problem points of the questions that they will solve, and know how to solve them, which formula to use, how the sequence of work is done, and perform calculations correctly.